Effects of Phase Selection on Gas-Sensing Performance of MoS2 and WS2 Substrates - Cao, Jiamu; Zhou, Jing; Chen, Junyu; Wang, Weiqi; Zhang, Yufeng; Liu, Xiaowei (ACS omega, 2020)
Two-dimensional transition metal disulfides such as MoS2 and WS2 exhibit multiple phases. Altering their phase makes it possible to change their chemical and physical properties significantly. Although several phase-induced modification mechanisms have been reported, their effects on the gas-sensing performance of these substrates remain unknown. Here, the effects of phase selection on the gas-sensing characteristics of 1T′ and 2H monolayer MoS2 and WS2 were explored using a density functional theory-based first-principles approach. The theoretical computations took into account the binding energy, band structure, theoretical recovery time, density of states, electron difference density, and total electron density. The results showed that there is a significant change in the density of states near the Fermi level as well as greater charge transfer between the gas in question and the substrate when the gas is adsorbed onto 1T′ MoS2 and WS2. Thus, phase selection is important for improving the gas-sensing performance of monolayer MoS2 and WS2. This study provides theoretical evidence for increasing the sensing performance of polymorph films of these materials.